Implementation of the Prosperous Rice Management Program for the Welfare of the Poor in Macanre Subdistrict - Halijah, Andi; Nur, Andi Cudai; H, Herman (Program Pascasarjana Universitas Negeri Makassar, 2024)
This research aims to examine the implementation of the prosperous rice management program on the welfare of the poor in Macanre Village, Soppeng Regency. This type of research is descriptive quantitative. Data collection techniques were carried out using observation, questionnaires and documentation. Data collection techniques were carried out by means of observation, questionnaires and documentation. The data analysis techniques used consist of instrument validation and reliability tests, descriptive statistical analysis, data normality tests and inferential statistical analysis. The results of the research show that the implementation of the Prosperous Rice Management Program has been carried out well, with a percentage value of 75%, and the welfare of the Poor in Macanre Village, Soppeng Regency is in the good category with a percentage value reaching 62%. The implementation of the Prosperous Rice Management Program has had a significant influence on the welfare of the poor in Macanre Village, Soppeng Regency with an influence percentage of 14.3% in the Low category.